Kewenangan dan Tanggung Jawab Notaris Pengganti setelah Pelaksanaan Tugas dan Jabatan Berakhir - Tengku Erwinsyahbana; Melinda Melinda (Lentera Hukum, 2018)
Abstract As an honorable position and profession, the notary replacement also has obligations that must be implemented, either based on laws and regulations that specifically regulate notary public (UUJN), or other laws and regulations. The authority of a notary substitute shall be the same as that of a notary public, comprising of general authority, special powers, and powers that shall be determined later in accordance with the laws and regulations. The replacement notary's legal liability includes civil liability, criminal responsibility, UUJN-based responsibilities, and responsibility for performing his / her duties under the Notary's Code of Conduct. However, the limitation of the length of time the substitute notary's responsibility to the deeds he made, has not been explicitly regulated in the UUJN. Keywords: Deed, Authority, Notary Substitute, Responsibility